Composite morphological structural element in the edge detecting - Arkadiusz Rajs; Mariusz Aleksiewicz; Agnieszka Goździewska-Nowicka; Krystyna Parczyk (Kazimierz Wielki University, 2017)
Rajs Arkadiusz, Aleksiewicz Mariusz, Goździewska-Nowicka Agnieszka, Parczyk Krystyna. Composite morphological structural element in the edge detecting. Journal of Education, Health and Sport. 2016;6(11):299-304. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167138 http://ojs.ukw.edu.pl/index.php/johs/article/view/3996       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 16.11.2016.       COMPOSITE MORPHOLOGICAL STRUCTURAL ELEMENT IN THE EDGE DETECTING   dr inż. Arkadiusz Rajs Institute of Telecommunications and Computer Science, University of Science and Technology, Al. Prof. S. Kaliskiego 7, 85-789 Bydgoszcz, arajs@utp.edu.pl dr inż. Mariusz Aleksiewicz Institute of Telecommunications and Computer Science, University of Science and Technology, Al. Prof. S. Kaliskiego 7, 85-789 Bydgoszcz,, mariusz.aleksiewicz@utp.edu.pl dr Agnieszka Goździewska-Nowicka University of Science and Technology, Faculty of Management, ul. Fordońska 430, 85-790 Bydgoszcz, Agnieszka.Gozdziewska@utp.edu.pl dr Krystyna Parczyk WSB University in Toruń, ul. Młodzieżowa 31a, 87-100 Toruń, krystyna.parczyk@wsb.torun.pl     Summary. Edge detection is an important step in image analysis. Using mathematical morphology and individual structural elements can detect certain types of edges. But much remains undetected. This paper proposes edge detection algorithm based on the structural element made up of many individual structure elements. The experimental results are showing.   Key words: mathematical morphology, edge detection